PENGARUH PEMBERIAN EKSTRAK Saccharomyces cerevisiae Hansen TERHADAP KANDUNGAN GOSIPOL PADA KULTUR KALUS Gossypium hirsutum L. - Sitinjak, Rama Riana; Siregar, Arbayah H; RE, Rizkita (Research Center for Biology-Indonesian Institute of Sciences, 2000)
This study concentrated on the effect of Saccharomyces cerevisiae Hansen extract on gosipol content of Gossypium hirsutum L callus cultures. There were many ways commonly used to obtain high secondary metabolites product by using tissue culture,i.e. elicitation.The objective of this study was to increase the production ofgossypol on G. hirsutum callus cultures using elicitor derived from S. cerevisiae.The callus grew optimally and produced gossypol on Linsmaierand Skoog (LS) medium with the addition of 10 M NAA and 10 M 2,4-D. Callus derived from cotyledon was subcultured five times.Callus was then elicited with elicitor derived from autoclaved S. cerevisiae and concentration of elicitor tested were 0.5, 1.0 and 2.5% (b/v). The harvesting times were 0, 2, 4, dan 6 days after elicitation. The gossypol was analyzed qualitatively and quantitatively by using High Performance Liquid Chromatography (HPLC).Gossypol content was influenced significantly by concentration of elicitor and harvesting time.The maximum ofgossypol content was obtained on the 4 day after elicitation i.e. 469.233 Â± 2.332 pg/g dry weight in the elicited callus of G. hirsutum.